Intranasal Low-Dose Naltrexone Against Opioid Side Effects: A Preclinical Study - Micheli, Laura; Di Cesare Mannelli, Lorenzo; Lucarini, Elena; Parisio, Carmen; Toti, Alessandra; Fiorentino, Bruno; Rigamonti, Maria Adele; Calosi, Laura; Ghelardini, Carla (Frontiers in Pharmacology, 2020)
Opioids are broad spectrum analgesics that are an integral part of the therapeutic armamentarium to combat pain in the clinical practice. Unfortunately, together with analgesia, a number of adverse effects can occur such as nausea, vomiting, constipation, gastrointestinal alterations and cognitive impairments. Naltrexone is a competitive antagonist of opioid receptors commonly used to treat opioid addiction; its oral use against agonists side effects is limited by the decrease of opioids-therapeutic efficacy and own adverse effects. The intranasal delivery of naltrexone could offer a quick and effective achievement of CNS based on extracellular mechanisms including perineural and perivascular transport. The aim of the study was to test the efficacy of intranasal low-dose naltrexone in reducing intraperitoneal morphine and oxycodone side effects in rodents. In mice, 1 μg naltrexone intranasally administered 30 min before opioids reduced cognitive impairments and motor alteration induced by 10 mg kg−1 morphine and 60 mg kg−1 oxycodone in the Passive avoidance and Rota rod tests, respectively. Moreover, naltrexone rebalanced opioid-induced reduction of the intestinal transit and latency of feces expulsion as well as food intake inhibition. Importantly, 1 μg naltrexone instillation did not block analgesia as demonstrated by the Hot plate test. In rats, intranasal naltrexone counteracted the opioid-induced pica phenomenon related to emesis and increased water and palatable food intake. The effects were comparable to that achieved by metoclopramide used as reference drug. Treatments did not influence body weight. Lastly, the safety of the intranasal delivery has been checked by hematoxylin–eosin staining that did not show histological alterations of the nasal cavity. In conclusion, intranasal low-dose naltrexone counteracted morphine and oxycodone induced gastrointestinal and CNS side effects without impairing opioid analgesia. It is a candidate to be a valid clinical strategy deserving deep analysis.